2021
DOI: 10.54476/iimrj301
|View full text |Cite
|
Sign up to set email alerts
|

New Normal Transition: Senior High School Teachers’ Percipience on its Ways and Challenges

Abstract: The incursion of COVID-19 to various states has set forth the challenge for the educational institutions to transition to the New Normal teaching and learning scheme. In the scarce of the studies driven by the perception of Senior High School (SHS) teachers on its ways and challenges using learning management system (LMS), this qualitative study was conducted. Specifically, the study aimed to explore the strategies and methods of teachers using LMS in (a) facilitating and (b) assessing learning; and (c) to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A researcher-made questionnaire with open-ended questions related to the informants' perceptions and experiences in learning biochemistry courses were utilized in this study. The researchers reviewed relevant literature to serve as a basis for instrument development (Rodriguez, 2021) in terms of its reliability and validity. Items formulated as part of the questionnaire were pursued to answer each research question which was divided into three.…”
Section: Instrumentmentioning
confidence: 99%
“…A researcher-made questionnaire with open-ended questions related to the informants' perceptions and experiences in learning biochemistry courses were utilized in this study. The researchers reviewed relevant literature to serve as a basis for instrument development (Rodriguez, 2021) in terms of its reliability and validity. Items formulated as part of the questionnaire were pursued to answer each research question which was divided into three.…”
Section: Instrumentmentioning
confidence: 99%
“…Consequently, Munoz et al (2021) found those neophyte teachers were not familiar with online education, as well as distance and hybrid learning. Hence, Rodriguez (2021) concluded that neophytes' online teaching is related to the number of years they spent as teachers.…”
Section: Introductionmentioning
confidence: 99%